El uso de las laptops XO en el área de Comunicación Integral en alumnos de educación primaria de una escuela rural en la región Junín-Perú - Gutiérrez García, Giovanna Aída (2010)
The present study analyzes the use of XO laptops as a tool of information technology and communication in language learning in the sixth grade students of a Peruvian rural school. To develop this study were applied activities and tools that show the students have a domain in the handle of this kind of laptops.